Effect of irrigation scheduling and nutrition on yield attributes, pod yield and economics of summer cowpea - kumar, Dilip; Patel, Ramdas; Kumar, Vikas; Sharma, Rajendra Kumar; Chaudhary, Dhawal Kumar; Patel, Mahesh Manilal (Annals of Agricultural Research, 2018)
A field experiment was conducted at the Agricultural Research Station, Ladol, Gujarat, India, onsummer cowpea (Vigna unguiculata [L.] Walp.) to study the Effect of irrigation scheduling andnutrition on yield attributes, yield and economics. The experiment was laid out in split plot designwith four replications during summer season (March to June), 2013-14, 2014-15 and 2015-16. Theexperiment consisted three irrigation treatments viz. IW/CPE ratio 0.8, 1.0 & 1.2 and three fertilitylevels namely, 100% RDF (25:50:00 NPK kg/ha), 100% RDF + Rhizobium + PSB and 75% RDF +Rhizobium + PSB. Among the different irrigation levels crop irrigated at 1.2 IW/CPE ratio recordedsignificantly higher pod numbers/plant (~51), pod weight/plant (206.9 g), length of pod (14.2 cm)and pod yield (10.79 t/ha) of cowpea as compared to IW/CPE ratio of 0.8. The increase in green podyield of cowpea due the application of irrigation water at 1.2 IW/CPE ratio was 31% and 4% highercompared to crop irrigated at 0.8 IW/CPE ratio and 1.0 IW/CPE ratio, respectively. Cowpea fertilizedwith 100% RDF + Rhizobium + PSB produced the significantly higher yield of green pod (10.34 t/ha) over 100% RDF (25:50:00 NPK kg/ha) (9.06 t/ha) and remain at par with 75% RDF + Rhizobium+ PSB (10.02 t/ha). The pod yield increased with the application of 100% RDF + Rhizobium + PSBwas 14% and 3% higher as compared to 100% RDF and 75% RDF + Rhizobium + PSB, respectively.Cowpea irrigated at IW/CPE ratio of 1.0 and fertilized with 100% RDF + Rhizobium + PSB hadresulted in highest net benefit: cost ratios of 2.74 and 2.70, respectively.